Zercon kadiri sp. n., a new oligophagous mite from Eastern Anatolia (Acari: Mesostigmata: Zerconidae). Issue 3 (3rd July 2019) - Karaca, Mehmet
Abstract : A new species of the family Zerconidae, Zercon kadiri sp. n., is described based on female, male, deutonymph and protonymph specimens. The material was collected in litter and soil under stone pines ( Pinus pinea ) in the Malatya Province of Turkey. The similarities and differences between the related species within the same genus are discussed.http://www.zoobank.org/urn:lsid:zoobank.org:pub:C56027B1-4A4B-4018-83B6-04B41A4C51FC